(untitled) (Journal of Universal Excellence, 2026)
Research Question (RQ): Bibliometric studies provide a useful tool in reviewing scientific research, by using quantitative methods for analyzing all available publications in a research area of interest, in our case research on smart factories. Therefore, the following research questions occurred: 1. how much research has been done on smart factories, since the concept first appeared in 2011? 2. what characterizes the available publications? Purpose: The purpose of our study is to analyze the extent of the available literature on the topic of smart factories, along with classifying the characteristics of available contributions, namely journal papers, conference papers and book chapter, along with their impact indicators. Method: Bibliometric analysis and historical literature review was done with the help of the Clarivate Analytics Web of Science bases: SCI-EXPANDED, SSCI, A&HCI, CPCI-S, CPCI-SSH, BKCI-S, BKCI-SSH, ESCI, CCR-EXPANDED, and IC. Results: We found that there are a total of 123 contributions to the field of smart factory research, from 2011 till 2017, and that most of these contributions fall under engineering and other technology related research areas, while a few fall within the social science category. Organization: Our study can help traditional factories and emerging smart factories learn about developments in the field of new smart technologies and learn information that might help them change their business models. Society: The number of citations helps determine the impact a paper or set of papers has had on a particular field of research or science in general, which can help other authors determine which papers might be useful for their own research. Originality: Up-to-date bibliometric analysis of Web of Science literature in the field of smart factories. Limitations / further research: Bibliometric studies only provide information on whether or not other authors found particular publications useful and do not provide information on why the publications were useful to those authors. Bibliometric studies thus serve a descriptive role and not a prescriptive role.